Cognitive rehabilitation using immersive virtual reality at young age: A case report on traumatic brain injury. Issue 3 (2nd July 2020) - De Luca, Rosaria; Portaro, Simona; Le Cause, Maria; De Domenico, Carmen; Maggio, Maria Grazia; Cristina Ferrera, Maria; Giuffrè, Grazia; Bramanti, Alessia; Calabrò, Rocco Salvatore
Abstract: Adolescents having moderate to severe traumatic brain injury (TBI) often experience long-lasting cognitive, emotional, and behavioral problems. In current clinical practice, rehabilitation techniques to treat cognitive abnormalities may be classified in two main categories, i.e. conventional or advanced. Aim of this case study was to evaluate the safety and efficacy of an immersive virtual environment (Computer Assisted Rehabilitation Environment [CAREN]), in a young boy affected by severe TBI. A 15-year-old boy with TBI involving the right parietal-temporal region underwent two different rehabilitation trainings, including standard cognitive rehabilitation alone in a usual clinical setting (face-to-face intervention with a paper and pencil approach) or the same cognitive program using virtual scenarios by means of CAREN. We evaluated the patient's cognitive status, before and after the two different trainings, by using a specific psychometric battery to evaluate the cognitive and behavioral functioning, such as attention abilities, visuo-spatial and executive functions. Only at the end of the CAREN training, we observed a significant improvement in specific cognitive and motor domains, such as attention abilities, visuo-executive processes, emotional awareness, and balance. Cognitive training, using immersive Virtual Reality, may be a useful tool to facilitate cognitive recovery in TBI patients.